Malignant Range Elevation of Serum Chromogranin A due to Inadvertent Use of Proton Pump Inhibitor in a Subject with Pancreatic Incidentaloma - Usman Hammawa Malabu; Rozemary Karamatic; Gillian Mahy; Kunwarjit Singh Sangla (Case Reports in Endocrinology)
We present a case of highly elevated tenfold rise of serum chromogranin A in a young, morbidly obese, hypertensive female being investigated for pancreatic mass, weight loss, and elevated ESR. Following extensive noninvasive investigations, an ultrasound-guided pancreatic biopsy confirmed benign haemorrhagic cyst. A clue to the etiology of the hyperchromogranin A was the elevated serum gastrin level leading to suspicion of proton pump inhibitor administration confirmed by admittance to its use. Withdrawal of the medication led to dramatic resolution of the neuroendocrine tumor marker.